Correlation between Husband's Perception and Support with Wife's Interest in Using Modern Contraception in Couple Unmet Need - Belinda Anindita; Ervi Husni; Sutio Rahardjo (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Unmet need are couples of childbearing age who are not using contraception but who wish to postpone the next birth (spacing) or stop childbearing altogether (limiting). unmet need in Indonesia reached 10.6% and East Java Province reached 7.7%. The number of unmet need in KB Sidotopo Village RW 05 was 27.8% and RW 12 was 35.9%. This study aims to determine the correlation between husband's perception and support with wife's interest in using modern contraception in couple unmet need. This study used a cross-sectional design. The population was reproductive-age couples whose unmet needs. A total of 159 couples was taken by purposive sampling technique. The instrument used was a questionnaire. To analyze used Spearman Rank Test with (0.05). The result shows that the husband's perception is (50.9%) negative, the husband's support is (57.2%) unsupportive, and the wife's interest (39.0%) is low. The results using the Spearman Rank test of husband's perception obtained a p-value of 0.000 < (0.05), which means a correlation between husband's perception and wife's interest in unmet need. For the husband's support, the p-value is 0.000 < (0.05), which means that there is a correlation between husband's support and wife's interest in unmet need. This research is useful to make couples of childbearing age aware of the importance of family planning. It is hoped that couples of childbearing age can obtain and seek more information about family planning.